Modeling of SGLT1 in Reconstituted Systems Reveals Apparent Ion-Dependencies of Glucose Uptake and Strengthens the Notion of Water-Permeable Apo States - Barta, Thomas; Sandtner, Walter; Wachlmayr, Johann; Hannesschlaeger, Christof; Ebert, Andrea; Speletz, Armin; Horner, Andreas (Frontiers in Physiology, 2022)
The reconstitution of secondary active transporters into liposomes shed light on their molecular transport mechanism. The latter are either symporters, antiporters or exchangers, which use the energy contained in the electrochemical gradient of ions to fuel concentrative uptake of their cognate substrate. In liposomal preparations, these gradients can be set by the experimenter. However, due to passive diffusion of the ions and solutes through the membrane, the gradients are not stable and little is known on the time course by which they dissipate and how the presence of a transporter affects this process. Gradient dissipation can also generate a transmembrane potential (VM). Because it is the effective ion gradient, which together with VM fuels concentrative uptake, knowledge on how these parameters change within the time frame of the conducted experiment is key to understanding experimental outcomes. Here, we addressed this problem by resorting to a modelling approach. To this end, we mathematically modeled the liposome in the assumed presence and absence of the sodium glucose transporter 1 (SGLT1). We show that (i) the model can prevent us from reaching erroneous conclusions on the driving forces of substrate uptake and we (ii) demonstrate utility of the model in the assignment of the states of SGLT1, which harbor a water channel.